Public Acceptance of Congestion Charging: Evaluating Feasibility as a Policy Response to Urban Traffic Congestion - Tan, Eng-Hwa; Hong, Meenchee; Saleem, Faiza (Journal of Entrepreneurship, Business and Economics, 2025)
Traffic congestion represents a critical challenge in cities undergoing rapid urbanization. This study investigates the factors influencing public acceptability of congestion pricing in Penang, Malaysia, recognized as one of the most rapidly developing urban regions in the nation. Using purposive sampling, survey data were gathered from 397 respondents and analyzed with an ordered logit model to identify key determinants of acceptance. Variables examined include trust in government, awareness of congestion issues, perceived fairness, anticipated travel time savings, and socio-demographic characteristics. Contrary to findings from the majority of existing studies, trust in government, identified as the predominant factor, did not have a significant influence on the acceptability of congestion pricing in Penang, possibly due to the high trust levels of the populace in the current administration. The results reveal that most residents are inclined to accept a congestion charge, with the acceptable price range estimated at RM0.50 to RM0.60 per kilometer of travel. Notably, awareness, equitable pricing, travel time savings, and gender emerged as significant predictors of acceptance. These findings provide valuable insights for designing equitable and effective congestion pricing schemes and may guide policymakers in developing strategies that improve traffic flow, enhance public transport investment, and reduce the marginal social cost of congestion. This study contributes to the broader literature on sustainable urban mobility and pricing policies. Research Paper Keywords: Traffic Congestion; Congestion Charge; Trust; Fairness; Awareness; Marginal Cost Reference to this paper should be made as follows: Tan, E.H., Hong., M.& Saleem, F. (2025). Public Acceptance of Congestion Charging: Evaluating Feasibility as a Policy Response to Urban Traffic Congestion. Journal of Entrepreneurship, Business and Economics , 13 (2), 118–153.